Putting brain training to the test - Owen, Adrian M. (2010)
‘Brain training’, or the quest for improved cognitive function through the regular use of computerised tests, is a multimillion pound industry1, yet scientific evidence to support its efficacy is lacking. Modest effects have been reported in some studies of older individuals2,3 and preschool children4, and video gamers out perform non-gamers on some tests of visual attention5. However, the widely held belief that commercially available computerised brain trainers improve general cognitive function in the wider population lacks empirical support. The central question is not whether performance on cognitive tests can be improved by training, but rather, whether those benefits transfer to other untrained tasks or lead to any general improvement in the level of cognitive functioning. Here we report the results of a six-week online study in which 11,430 participants trained several times each week on cognitive tasks designed to improve reasoning, memory, planning, visuospatial skills and attention. Although improvements were observed in every one of the cognitive tasks that were trained, no evidence was found for transfer effects to untrained tasks, even when those tasks were cognitively closely related.